1989
DOI: 10.1007/bf01929212
|View full text |Cite
|
Sign up to set email alerts
|

Satellited chromosome 9 in a boy with multiple anomalies

Abstract: SummaryA 5-year-old boy with multiple congenital anomalies showed a satellited long-arm chromosome 9, a previously undescribed abnormality. Various banding analyses of his chromosomes and those of his parents indicated that a reciprocal translocation, t(9 ;22)(q34.3 ;ql 1.21), occurred in the father's gonad, and one of the translocation chromosomes was then transmitted to the patient. Thus, the patient's karyotype was interpreted as 46,XY,-9,+psudic(9),t(9;22)(q34.3;qll.21). He showed several features similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…We previously reported five unrelated patients with a 9q34.3 deletion (Dawson et al 2002;Iwakoshi et al 2004). In addition, we found another, which was previously reported as a MCA/MR case of satellited chromosome 9 (Harada et al 1989). All of these patients shared several distinctive anomalies, which are likely to have their origin in a deletion overlap region at distal 9q34.3.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…We previously reported five unrelated patients with a 9q34.3 deletion (Dawson et al 2002;Iwakoshi et al 2004). In addition, we found another, which was previously reported as a MCA/MR case of satellited chromosome 9 (Harada et al 1989). All of these patients shared several distinctive anomalies, which are likely to have their origin in a deletion overlap region at distal 9q34.3.…”
Section: Introductionsupporting
confidence: 59%
“…We analyzed six patients with 9q34.3 terminal deletions, and their karyotypes were 46,XY,der(9)t(9;22) (q34.3;q11.21)de novo (Case A: originally described as a case report by Harada et al 1989), 46,XX. ish del(9)(q34.3)de novo (Case B: described as Patient 1 in Iwakoshi et al 2004), 46,XY.…”
Section: Subjectsmentioning
confidence: 99%
“…It is thought that the DNA sequence in the short arms of acrocentric chromosomes is more likely to recombine with the sequence in the terminal 4q [Miller et al, 1995]. There are also reports identifying a satellite structure on other non-acrocentric chromosomes [Dev et al, 1979;Verma et al, 1979;Varley et al, 1981;Kucerova et al, 1983;van Tuinen et al, 1983;Schmid et al, 1984;Stetten et al, 1986;Harada et al, 1989;Arn et al, 1995;Faivre et al, 1999;Guttenbach et al, 1999;Storto et al, 1999;Lee et al, 2001;Willatt et al, 2001;Ki et al, 2003;Chen et al, 2004a,b] with one report on 15q which occurred as a mosaicism with ring chromosome 15 [Smith et al, 1991]. The majority of cases are familial and are detected during prenatal diagnosis [Chen et al, 2000[Chen et al, , 2004aLee et al, 2001].…”
Section: Discussionmentioning
confidence: 93%
“…This type of translocation has been reported either as rare familial polymorphisms having no phenotypic effect or de novo translocations with chromosomal loss causing abnormalities. There are several previous reports of satellited autosomes [Parslow et al, 1979;Verma et al, 1979;Watt et al, 1984;Harada et al, 1989;Estabrooks et al, 1992;Arn et al, 1995;Willatt et al, 2001;Ki et al, 2003;Chen et al, 2004a,b]. The most frequent satellited variant autosomes reported to date is chromosome 4 (4qs) [Estabrooks et al, 1992;Arn et al, 1995;Miller et al, 1995;Guttenbach et al, 1999].…”
Section: Introductionmentioning
confidence: 93%
“…qter deletion or duplication without the involvement of another chromosome. Harada et al [1989] has described a case with similar de novo unbalanced translocation with comparable breakpoints, and recent molecular delineation of the breakpoint in the same patient by Harada et al [2004] showed that the deletion is larger than the shortest 1Mb deletion region overlap in other patients investigated in their recent studies. As seen from the CGH microarray studies, our patient also demonstrated a deletion exceeding this smallest deleted region (Fig.…”
Section: Discussionmentioning
confidence: 94%